Prognostic significance of thyroid dysfunction in acute stroke - Shivashankara Kaniyoor Nagri; Chandrasekhar Udayavara Kudru; Sampath Kumar Amaravadi; Laxmi Prasad (Wolters Kluwer Medknow Publications, 2021)
Background: Cerebrovascular accidents (CVAs) are the leading cause of morbidity and mortality. Several comorbidities have been associated with increased mortality in acute stroke patients. Conditions such as hypertension, dyslipidemia, diabetes mellitus, and thyroid dysfunction are identified as risk factors in the etiology of stroke. Methods: This is a prospective study involving 40 patients admitted with acute stroke between October 2010 and July 2012 in Kasturba Hospital, Manipal, under the Departments of Medicine and Neurology. Results: Thyroid dysfunction has been associated with CVAs and is an area of active research in the present times. Conclusion: Low T3 level was associated with unfavorable outcome and with posterior circulation stroke as accessed using the National Institutes of Health Stroke Scale.